2009
DOI: 10.1016/j.mce.2009.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Selective labeling of IRAP by the tritiated AT4 receptor ligand [3H]Angiotensin IV and its stable analog [3H]AL-11

Abstract: 'AT(4) receptors' through which Angiotensin IV (Ang IV) improves memory acquisition, were recently identified as insulin regulated aminopeptidase (IRAP). Radioligand binding studies have hitherto been performed with iodinated Ang IV in the presence of divalent cation chelators EDTA and 1,10-phenanthrolin. Hence, they referred to the apo-form of IRAP. Presently, binding of [(3)H]Ang IV and [(3)H]AL-11, a stable Ang IV analog, was compared on Chinese hamster ovary (CHO-K1) and mouse hippocampal (P40H1) cell memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 33 publications
0
33
2
Order By: Relevance
“…Because many known neuropeptides function through G-protein coupled receptors, a reasonable strategy to explore potential functions would be to screen cell lines expressing receptors (both known and “orphan”) with the secretory pathway peptides listed in Table S1. However, it is also possible that peptides bind to other extracellular targets and exert a biological effect independent of G-protein coupled receptors; there are examples where the biological activity of peptide is thought to be through inhibition of enzymes rather than through interactions with receptors 35,36,37,38,39…”
Section: Discussion: Implications Speculation and Further Directionsmentioning
confidence: 99%
“…Because many known neuropeptides function through G-protein coupled receptors, a reasonable strategy to explore potential functions would be to screen cell lines expressing receptors (both known and “orphan”) with the secretory pathway peptides listed in Table S1. However, it is also possible that peptides bind to other extracellular targets and exert a biological effect independent of G-protein coupled receptors; there are examples where the biological activity of peptide is thought to be through inhibition of enzymes rather than through interactions with receptors 35,36,37,38,39…”
Section: Discussion: Implications Speculation and Further Directionsmentioning
confidence: 99%
“…The compound solutions (75 nl) were dispensed directly into columns 1-22 of the assay plates (242757; Nunc) by using an Echo 555Ô acoustic liquid handler (LabCyte). The Echo was also used to dispense the equivalent volume of DMSO (negative control, 0% inhibition), and a 10 mM DMSO solution of AL-11 19,33 (positive control, 100% inhibition), in columns 23 and 24, with DMSO in rows A-H and AL-11 in rows I-P. The final compound concentration used in the screen was 10 mM, with a final DMSO concentration of 0.1% in all wells.…”
Section: Compound Library Storage and Handlingmentioning
confidence: 99%
“…It was suggested that the differences were a result of the absence of zinc in the active site when metal chelators were present [159, 164166]. Thus, it became obvious that chelators must be omitted to obtain physiologically relevant results [167]. Furthermore, the results illustrated also the importance of synthesising inhibitors that are metabolically stable and are not substrates of IRAP.…”
Section: Inhibitors Of Insulin-regulated Aminopeptidasementioning
confidence: 99%
“…Ang IV itself is only a weak inhibitor of the catalytic activity of IRAP, as has been shown by experiments with the metabolically stable tritiated Ang IV analogue [ 3 H]AL-11, in combination with the selective AP-N inhibitor 7B which is a phosphinic transition-state analogue [171] and in the absence of metal chelators. Adding metal chelators creates the apoform of IRAP [167, 172], and it is important to note that the active form and apoforms of IRAP react differently [173]. Hence, much of the previous results refer to binding to the apoenzyme rather than to the catalytically active enzyme [122124, 174].…”
Section: Inhibitors Of Insulin-regulated Aminopeptidasementioning
confidence: 99%